Gestão dialógica: um estudo a partir das comunidades de aprendizagem - Santos, Andréia Oliveira Ferreira dos (2016)
This study aims to analyses the ONG/Escola management, its impasse concerning the students learning administration. The place where the study occurs is the ONG/Escola, localized at São Paulo´s east zone. The school administration is the study subject, and it brings to us some questions: how we can overcome an education model that is concerned with the results administration? How we can overcome a school administration which the main purpose is the meritocracy? How we can develop an educational purpose which the main administration purpose is the participation of all and the dialog? After the analyses, the aspect of a bureaucratic and management administration was established, therefore a dialogic management project was presented, it is according the Comunidades de Aprendizagem project (Learning Community project), that proposes to manage the school through dialog, in order to improve learning, promoting the dialogic participation in the learning management with all the scholar community. To do this, the study has two movements. The first one consist of the management analysis results that happened in the school, and the second consist of the first results from the “new” dialogical management, its references are the Habermas´s theory, concerning the communicative action concept, and Freire´s theory about dialogicity. This work was made using the critical communicative methodology, the main instruments to data collect were the observations and communicative reports, it involved the intersubjective analysis of them, and the official documents analysis that legalize the school. The dialogical process that was applied in ONG/Escola showed clearly that the school management, by recognizing the participants of its community, the school knowledge must be developed in support of rights equality, the possible world transformation and dialogic practice. A process that came with a viable and possible possibility, that implies in deals, negotiations, compromises, that lead to autonomy and emancipation.